KAJIAN BEBERAPA TINGKAT CEKAMAN KEKERINGAN TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH LOKAL NTT - Vinni D. Tome; Chatlynbi Pandjaitan; Nimrot Neunufa (Partner, 2016)
Development of shallot in NTT is closely related to the utilization of dry land that highly susceptible to drought stress. The growth and yield of shallot on drought condition depended on the level of stress experienced all phases of shallot and the genetic capability of each shallot cultivars. The objective of this study is to determine the growth and yield of local shallots NTT with several drought conditions. The experiment had been conducted from April to December 2015, using a randomized block design group. The treatment consisted of two factors which were the level of drought stress and cultivars of local shallots from NTT. Data were analyzed using ANOVA and Duncan Multiple 0.05. The results showed that the water supply upto 75% of field capacity was still able to support the growth of shallot in the form of plant height and number of leaves, while the number of tillers and number of tubers was generated by the provision of water 50% of field capacity. The highest result was shown by cultivars from Rote and Sabu both on the supply of water of 100%, XGeneve 75% and 50% of field capacity. Cultivars Rote, Sabu and Semau were not able to generate decent harvested tubers on condition of water supply 25% of field capacity.Keywords: Drought, Growth and Yield, Local Shallots from NTT